Contemporary comics storytelling - Kukkonen, Karin (Frontiers of narrative series, 2013)
How to analyze comics cognitively -- Textual traditions in comics: fables, genre, and intertextuality -- Fictionality in comics: Tom Strong, storyworlds, and the imagination -- Fictional minds in comics: 100 bullets, characterization, and ethics